சங்க இலக்கியத் தத்துவங்கள் (PHILOSOPHIES OF SANGAM LITERATURES) - S., Kumaran (Journal of Indian Studies (இந்திய ஆய்விதழ்), 2020)
A few poems in the Sangam Literature by selected poets portray not just giving exploration of the normal literary explanations, but they also offers in-depth of ethical orders of the society by that time. The article has cited some of such songs with the philosophical thoughts found within the lines. There are many of such philosophical and ethical ideas found within those works. This essay is designed for the view that all the scholars of Sangam Literature who composed philosophical Tamil songs are philosophical geniuses. ஆய்வுச் சுருக்கம் சங்க இலக்கியப் பாடல்களில் புலவர்கள் சிலர் பாடிய அறப்பாடல்களுள் - நீதிமுறைப் பாடல்களுள் பொதிந்து கிடக்கின்றன. அவற்றுள் காணக்கிடக்கும் சில தத்துவார்த்தச் சிந்தனைகளை ஆதாரங்களோடு இக்கட்டுரை எடுத்துக் காட்டியுள்ளது. இத்தகைய பாடல்கள் போன்று மேலும் பல தத்துவார்த்தச் சிந்தனைகளை உணர்த்தும் அறப்பாடல்களும் உள்ளன. தத்துவம் பொதிந்த தமிழ்ப் பாடல்கள் இயற்றிய சங்ககாலத்துப் புலவர்கள் அனைவரும் தத்துவ மேதைகள் எனும் பார்வையில் இக்கட்டுரை வடிவமைக்கப்பட்டுள்ளது